Stability of Biologically Synthesized Silver Nanoparticles (AgNPs) Using Acalypha indica L. Plant Extract as Bioreductor and Their Potential as Anticancer Agents Against T47D Cells - Madaniyah, Luailik; Fiddaroini, Saidun; Hayati, Elok Kamilah; Rahman, Moh. Farid; Sabarudin, Akhmad (Science and Technology Indonesia, 2025)
This work investigates the anticancer potential of silver nanoparticles (AgNPs) against T47D cells as well as the stability of AgNPs manufactured using extract from Acalypha indica L. used as a bioreductant. The plant extract was used to produce and stabilize AgNPs, and stability was tracked for 30 days using UV-Vis spectroscopy and Particle Size Analysis (PSA), which included evaluations of extended sun exposure. Transmission Electron Microscopy (TEM) was used to characterize the size and shape of the nanoparticles, and Fourier Transform-Infrared Spectroscopy (FT-IR) was used to determine which functional groups were responsible for stabilization. Despite a gradual size increase, the AgNPs remained stable throughout the study period. The MTT assay confirmed their potent cytotoxicity against T47D cells, underscoring the potential of Acalypha indica-derived AgNPs as stable and effective agents for cancer therapy, offering a promising alternative for novel anticancer treatments.